Human rights in the Asia-Pacific region towards institution building - Nasu, Hitoshi; Saul, Ben (London Routledge, 2011)
"The Asia-Pacific region is known for having one of the least developed institutional mechanisms for protecting human rights. This edited collection makes a timely and distinctive contribution to contemporary debates about strengthening the institutional protection of human rights in the Asia-Pacific region, in the wake of ASEAN's announcement in 2009 of an ASEAN regional human rights mechanism.Drawing together leading scholarly voices, the book focuses on the systemic issue of institutionalising human rights protection in the Asia-Pacific. It critically examines the prospects for deepening and widening the institutionalization of human rights monitoring in the region, challenging the orthodox scepticism about whether Asia is "ready" for stronger institutions. The volume analyses the impediments to institutions, whilst questioning the need for them. The collection provides a range of perspectives on the issues and many of the chapters bring a variety of interdisciplinary insights to bear. As such, the collection will be of interest to a scholarly and student audience in law, as well as to readers in international relations, political science, Asian studies, and human rights"--
"The Asia-Pacific is known for having the least developed regional mechanisms for protecting human rights. This edited collection makes a timely and distinctive contribution to contemporary debates about building institutions for human rights protection in the Asia-Pacific region, in the wake of ASEAN's establishment in 2009 of a sub-regional human rights commission. Drawing together leading scholarly voices, the book focuses on the systemic issue of institutionalising human rights protection in the Asia-Pacific. It critically examines the prospects for deepening and widening human rights institutions in the region, challenging the orthodox scepticism about whether the Asia-Pacific is "ready" for stronger human rights institutions and exploring the variety of possible forms that regional and sub-regional institutions might take. The volume also analyses the impediments to new institutions, whilst questioning the justifications for them. The collection provides a range of perspectives on the issues and many of the chapters bring interdisciplinary insights to bear. As such, the collection will be of interest to scholarly, practitioner, and student audiences in law, as well as to readers in international relations, political science, Asian studies, and human rights"--
Persistent engagement and insistent persuasion : the role of the working group for an ASEAN human rights mechanism in institutionalising human rights in the region / Tan Hsien-Li -- ASEAN : setting the agenda for the rights of migrant workers? / Susan Kneebone -- Challenges for Asean human rights mechanisms : the case of Lao PDR from a gender perspective / Irene Pietropaoli -- The role of networks in the implementation of human rights in the Asia-Pacific region / Catherine Renshaw -- Human rights commissions in times of trouble and transition : the case of the national human rights commission of Nepal / Andrea Durbach -- Corporate human rights abuses : what role for the national human rights institutions? / Surya Deva -- Rethinking human rights in China : towards a receptor framework / Mimi Zou and Tom Zwart.
Includes bibliographical references and index.
Keywords: Human rights -- Asia; Human rights -- Pacific Area; National human rights institutions -- Asia; National human rights institutions -- Pacific Area; Law / General; Law / Civil Rights; Law / Comparative